Inhibition of Germinal Centre Apoptotic Programmes by Epstein-Barr Virus - Lindsay C. Spender; Gareth J. Inman (Advances in Hematology)
To establish a persistent latent infection, Epstein-Barr virus (EBV) faces a challenge in that the virus-infected host cell must transit through the germinal centre reaction. This is a site of B cell differentiation where antibody responses are optimised, and the selection criteria for B cells are stringent. The germinal centre environment is harsh, and the vast majority of B cells here die by apoptosis. Only cells receiving adequate survival signals will differentiate fully to be released into the periphery as long-term memory B cells (the site of persistence). In this review, we detail the apoptotic pathways potentially encountered by EBV-infected B cells during the process of infection, and we describe the functions of those EBV-regulated cellular and viral genes that help promote survival of the host B cell.